The Role of stakeholders in the development of tourism destinations in Gelora Bung Karno - Siregar, Fadli Ahmad Kurnia; Sinaga, Geoffrey Alexander; Wibowo, Mazaya Fathia Adreya; Azelia, Rifdah; Zakiyyah, Rizqi; Az Zahra, Sity Aidah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Gelora Bung Karno (GBK) in Jakarta has significant potential as a tourism destination, serving as a hub for sports, recreation, and events. Understanding the role of various stakeholders in the development of this destination is essential for achieving sustainable tourism growth. This study aims to analyze the role of stakeholders in shaping the development of GBK as a prominent tourism destination. Methods: The study utilized a qualitative approach to analyze the involvement of key stakeholders, including the government, tourism entrepreneurs, local communities, and sports organizations. Data was collected through interviews and document analysis, focusing on stakeholder collaboration in destination management and sustainability initiatives. Findings: The analysis reveals that strong cooperation among stakeholders is critical to the sustainable and inclusive development of GBK as a tourism destination. The government provides regulatory support, while the private sector contributes to infrastructure and service development. Local communities and sports organizations play a vital role in maintaining cultural relevance and ensuring that development meets community needs. Conclusion: The study concludes that a well-coordinated collaboration between stakeholders is essential for the sustainable development of Gelora Bung Karno as a tourism destination. Effective stakeholder engagement can lead to more inclusive tourism development, benefiting both the economy and the local population. Novelty/Originality of this study: This research provides valuable insights into stakeholder collaboration in the context of tourism development at Gelora Bung Karno, offering a model for other destinations in Indonesia seeking to implement sustainable tourism policies. The study highlights the importance of inclusive and multi-stakeholder approaches for achieving long-term success.